Transformation of Children's Rights After Divorce Outside the Religious Court of Padangsidimpuan City in the Perspective of Maslahah - Adi Syahputra Sirait; Muhammad Ridwan (al-Afkar, Journal For Islamic Studies, 2025)
Divorce is a problem that is quite complicated and very dilemmatic in people's lives. Although Law Number 1 of 1974 was promulgated and enforced 39 years ago, the reality is that the practice of divorce carried out by the husband is not in front of the Religious Court hearing. In Article 39 paragraph (1) of Law N0. 1 of 1974 states that divorce can only be done in front of a competent court after the court concerned has tried and cannot reconcile the two parties. To carry out a divorce, there must be enough reason, that between a man and a woman they will no longer be able to live in harmony as husband and wife. In fact, in the jurisdiction of the Religious Court of Padangsidimpuan City, there are still many who carry out divorces outside the Religious Court. This research method uses a juridical-normative method. The data sources used include primary legal materials, secondary legal materials and tertiary legal materials. After the data is collected, classified and processed, it will be compiled into a scientific paper. The results of this study show that the factors that cause divorce in the Padangsidimpuan City Religious Court are economic factors, community legal knowledge factors, juridical factors, sociological factors, and customary factors (kinship system dalihan na tolu). The mechanism of divorce is carried out by oral talaq, a written statement submitted to the wife, and secretly without anyone knowing it. As a result of the law that arises, the wife has difficulty getting a new marriage through the Religious Affairs Office (KUA), cannot claim living expenses through the Religious Court, it is difficult to get joint property and has a negative impact on the rights of the child who is the victim. Maslahah's view of the transformation of children's rights after divorce is prone to be ignored because the rights to alimony, education, health, and inheritance rights are not fulfilled. The obligation of parents as protectors and guides for children is good. Children do not receive complete affection from their father and mother.